Is Device-Measured Vigorous-Intensity Physical Activity Associated with Health-Related Outcomes in Children and Adolescents? a Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Elsevier B.V., 2021)
Objective: This study sought to analyze the prospective association between vigorous-intensity physical activity (VPA) and health-related outcomes in children and adolescents. Methods: Studies reporting associations between device-measured VPA and health-related factors in children and adolescents aged 3–18 years were identified through database searches (MEDLINE, EMBASE, and SPORTDiscus). Correlation coefficients were pooled if outcomes were reported by at least 3 studies, using DerSimonian-Laird random effects models. Results: Data from 23 studies including 13,674 participants were pooled using random effects models. Significant associations were found between VPA at baseline and overall adiposity (r = −0.09, 95% confidence interval (95%CI): –0.15 to –0.03; p = 0.002; I2 = 89.8%), cardiometabolic risk score (r = –0.13, 95%CI: –0.24 to –0.02, p = 0.020; I2 = 69.6%), cardiorespiratory fitness (r = 0.25, 95%CI: 0.15−0.35; p < 0.001; I2 = 57.2%), and total body bone mineral density (r = 0.16, 95%CI: 0.06 to 0.25; p = 0.001; I2 = 0%). Conclusion: VPA seems to be negatively related to adiposity and cardiometabolic risk score and positively related to cardiorespiratory fitness and total body bone mineral density among children and adolescents at follow-up. Therefore, our findings support the need to strengthen physical activity recommendations regarding VPA due to its health benefits in children and adolescents. © 2021